Trade-offs and synergies of digital choice environments: Towards a taxonomy and configurational model - Phillip Oliver Gottschewski-Meyer; Marvin Auf der Landwehr; Nicole Lüddemann; Christoph von Viebahn (Electronic Markets, 2024)
The advancing digitalization of daily life has led to an increasing number of choices in the digital sphere. User interfaces that require either a judgment or a decision, the so-called digital choice environments (DCEs), are essential focal points for interventions to alter behaviors towards individual or societal welfare. However, there is a lack of descriptive and prescriptive knowledge within the field of DCEs. In this research, we follow a multi-stage approach to classify the characteristics of DCEs from a choice-centric viewpoint and disclose configurational trade-offs. To achieve this, we first build a taxonomy of DCEs that we validate through expert interviews. Subsequently, we use cluster analysis to identify four configurations of DCEs, which serve as the basis for the development of a configurational model that outlines configuration-specific user outcomes. Our results contribute to the existing knowledge of digital value creation as well as the explanatory understanding of trade-offs among different DCEs.
Keywords: D70; 620; Taxonomy; Digital choice environments; Configurational model